Identidade quilombola na formação de professores: um estudo de caso no curso de licenciatura em pedagogia na Comunidade Remanescente de Quilombo Igarapé do Lago - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
This dissertation aimed to investigate how quilombola identity was evident in teacher training for the Pedagogy Degree program at UNIFAP/Santana Campus in the Remnant Community of Quilombo Igarapé do Lago – AP, focusing on strengthening the being and living of the students who study there, as it is an affirmative action policy for ethnic-racial education in higher education, through the university extension project - Quilombola Interiorization Program – PIQ/UNIFAP. For this purpose, the question that underpinned the investigative actions was: How has quilombola identity been evident in teacher training, carried out by the Pedagogy Degree program at UNIFAP/Santana, in the remnant community of quilombo Igarapé do Lago? To obtain possible answers, the general objective was to analyze how quilombola identity has been evidenced in the teacher training provided by the Pedagogy Degree program at UNIFAP/Santana, in the Igarapé do Lago remnant quilombo community. From this perspective, the specific objectives were: 1. to contextualize the Igarapé do Lago community with its specificities inherent to a quilombo remnant community, addressing: intergenerational knowledge and practices, culture, and identity; 2. to debate whether the Quilombola Interiorization Program at UNIFAP proposes teacher training that values and connects with quilombola sociocultural knowledge; 3. to identify evidence of quilombola identity in the teacher training provided by the Pedagogy Degree program at UNIFAP/Santana, in the Igarapé do Lago remnant quilombo community. The method used was dialectical (Gadotti, 1990); (Gamboa, 2011); (Santos, 2002); (Castro, 2024), the method used was a single case study (Yin, 2010) and a qualitative approach (André, 2013) (Minayo, 2007). The data collection instruments were: documentary research (Chizzotti, 2000); (Gil, 2008), in-depth semi structured interviews (Manzini, 1990/1991); (Duarte, 2005), with semi-structured questionnaires and the support of voice recordings. The interlocutors were: a pedagogical coordinator of the course (coordinator of the PIQ Igarapé do Lago and a teacher); two teachers (involved with training at the university center); six academics (participants in quilombola social and cultural activism). The locus of the research was the remaining quilombo community of Igarapé do Lago. The data collected and organized were done through content analysis (Moraes, 1994/1999/2014). The main theoretical contributions used were: Silva (2014); Hall (2014); Gomes (2002); Munanga (2004/2009/2012); Silva (2010); Bath (2000); Souza (1983/2021); Fanon (2008); Kilomba (2019) Arroyo (2013), Saviani (1991/2013) and others. The research results showed that teacher training in Igarapé do Lago through the Quilombola Interiorization Program-PIQ/UNIFAP faced challenges and yet, the academic actions/activities corroborated the students' understanding of "being quilombola" and then affirming their quilombola identity.
Keywords: Igarapé do Lago; Educação Quilombola; Educação Étnico-Racial; CNPQ::CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL; ODS 10 – Redução das desigualdades; ODS 4 – Educação de qualidade; ODS 16 – Paz, justiça e instituições eficazes